Spread through air spaces may predict early progression after salvage surgery for EGFR-mutant advanced lung adenocarcinoma treated with targeted therapy - Yu-Wei Liu; Wei-An Lai; Jen-Yu Hung; Yen-Lung Lee; Hung-Hsing Chiang; Jui-Ying Lee; Hsien-Pin Li; Shah-Hwa Chou; Chih-Jen Yang (World Journal of Surgical Oncology)
Abstract Objective Salvage resection for residual lung cancer harboring epidermal growth factor receptor (EGFR) mutations following EGFR-tyrosine kinase inhibitor (TKI) treatment is gaining traction for its survival benefits. However, the impact of pathological factors on survival remains unclear. Methods Between 2013 and 2023, we retrospectively reviewed 34 patients with advanced lung adenocarcinoma who received EGFR-TKI therapy. After a median TKI treatment duration of 9.1 months, all patients demonstrated either partial response (n = 27) or stable disease (n = 7) before salvage surgery. Demographic, pathological outcomes, progression-free survival (PFS), and overall survival (OS) were analyzed. Results Among the 34 patients, six (17.6%) achieved a pathological complete response (pCR) and nine (26.5%) had a major pathological response (MPR). Additionally, 11 patients (32.4%) exhibited spread through air spaces (STAS), and lymphovascular invasion (LVI) was observed in nine patients (26.5%). The 3-year PFS and OS rates were 55.8% and 60.5%, respectively. No significant differences in PFS or OS were observed regarding mutation type, TKI generation, pCR, MPR, or LVI. However, Kaplan-Meier analysis revealed that STAS was associated with shorter PFS compared to non-STAS cases (p = 0.01). In multivariate analysis, STAS was identified as an independent prognostic factor for PFS (hazard ratio: 2.83, 95% CI: 1.35–28.54, p = 0.02). No significant prognosticators were found for OS in univariate or multivariate analyses. Conclusion While salvage surgery following TKI treatment is feasible and prolongs survival by removing residual primary tumor with potential TKI resistance, STAS may contribute to a higher risk of early progression. This finding warrants further investigation and tailored treatment strategies.